2023
DOI: 10.1093/nutrit/nuac114
|View full text |Cite
|
Sign up to set email alerts
|

Association between animal protein sources and risk of neurodegenerative diseases: a systematic review and dose-response meta-analysis

Abstract: Context Current findings about the differential effects of various sources of dietary animal protein on the risk of neurodegenerative diseases are contradictory. Objective The current meta-analysis was conducted to investigate the associations between intake of dietary animal protein sources and the risk of neurodegenerative diseases. Data Sources PubMed, Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 77 publications
1
8
0
Order By: Relevance
“…The relationship between red meat consumption and neurodegeneration and PD is still unclear. Our research identified a significant association between a preference for beef steak and an increased brain iron in motor regions as well as a decreased risk of PD; however, recent systematic reviews have found no association between red meat consumption and cognitive impairment, Alzheimer’s disease, dementia, or PD 100,101 . Results may be so variegated because the actual iron absorbed from a meat will vary based on the cut and cooking method 102 as well as the presence or absence of iron absorption inhibitors or promoters in the meal 103 .…”
Section: Discussionmentioning
confidence: 47%
“…The relationship between red meat consumption and neurodegeneration and PD is still unclear. Our research identified a significant association between a preference for beef steak and an increased brain iron in motor regions as well as a decreased risk of PD; however, recent systematic reviews have found no association between red meat consumption and cognitive impairment, Alzheimer’s disease, dementia, or PD 100,101 . Results may be so variegated because the actual iron absorbed from a meat will vary based on the cut and cooking method 102 as well as the presence or absence of iron absorption inhibitors or promoters in the meal 103 .…”
Section: Discussionmentioning
confidence: 47%
“…This allowed us to determine the effect size for each extra exposure serving. [42] We also implemented a nonlinear dose-dependent analysis applying limited cubic splines with three knots (10, 50, and 90 percentiles of the distribution). [43] We examined the correlation within every group of published RRs and then combined the study-certain estimates through a one-stage mixed effects analysis.…”
Section: Discussionmentioning
confidence: 99%
“…To cover broad medical fields, we selected three high-quality meta-analyses as validation datasets, which focused on inflammatory bowel diseases (IBD), 15 diabetes mellitus (DM), 16 and sarcopenia, 17 respectively ( Table 2 ). These meta-analyses provided clear search strategies for Medline/PubMed database and complete list of records that remained after screening based on their titles and abstracts.…”
Section: Methodsmentioning
confidence: 99%